KESEHATAN REPRODUKSI PADA ETNIS MINANGKABAU - Helpi Nelwatri (Kafa`ah: Journal of Gender Studies, 2014)
In this paper, the author looks at various cultural issues on health reproduction in relation to Minangkabau cultural perspective in the province of West Sumatra. Minangkabau is one of the ethnics which adopt matrilineal system. That is why then this paper wants to highlight the cultural issue that is related to the problem of health reproduction that is commonly found in social context of Minangkabau society. At least this short article discusses the issue of health reproduction and  and local wisdom, especially women’s problems of health reproduction. Keywords: Health, reproduction, and Minangkabau ethnicCopyright © 2014 by Kafa`ah All right reservedDOI :  10.15548/jk.v4i1.89